EDUKASI APOTEK HIDUP SEBAGAI SARANA PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN KEMANDIRIAN DAN LITERASI EKONOMI SISWA UPTD SD NEGERI 05 DESA PEMATANG PANJANG - Widya Saputri; Wan Dian Safina; Putri Rahayu Amanda Nasution; Arifna Luthfianida; Indra Sahputra; Hamzah Zai (LPPI UMN AL WASHLIYAH, 2025)
The purpose of this community service is to make a living pharmacy as an alternative herbal medicine that can maintain health and overcome complaints of various diseases among students of UPTD SD Negeri 05 Pematang Panjang Village. This education aims to examine the use of a living pharmacy as a contextual learning tool in an effort to increase the independence and economic literacy of students of UPTD SD Negeri 05 Pematang Panjang Village. The living pharmacy, which is a medicinal plant garden in the school environment, is used as an integrated learning medium based on real experiences that are relevant to the daily lives of students. The method of implementing the field research is by providing direct socialization of the creation of a living pharmacy in the UPTD SD Negeri 05 Pematang Panjang Village environment. Through the activities of planting, caring for, and utilizing medicinal plants, students not only learn about the benefits of plants scientifically, but are also trained to manage the results economically, such as through simple entrepreneurial activities. This education is expected to be the first step in building student awareness of the importance of utilizing the environment as a source of learning and economic empowerment. Keywords: Living Pharmacy, Contextual Learning, Economic Literacy.